Ligand‐induced expansion of the S1′ site in the anthrax toxin lethal factor. Issue 24 (11th November 2015) - Maize, Kimberly M.; Kurbanov, Elbek K.; Johnson, Rodney L.; Amin, Elizabeth Ambrose; Finzel, Barry C.
Abstract : The Bacillus anthracis lethal factor (LF) is one component of a tripartite exotoxin partly responsible for persistent anthrax cytotoxicity after initial bacterial infection. Inhibitors of the zinc metalloproteinase have been investigated as potential therapeutic agents, but LF is a challenging target because inhibitors lack sufficient selectivity or possess poor pharmaceutical properties. These structural studies reveal an alternate conformation of the enzyme, induced upon binding of specific inhibitors, that opens a previously unobserved deep pocket termed S1′ ∗ which might afford new opportunities to design selective inhibitors that target this subsite. Abstract : Structures of anthrax lethal factor with bound inhibitors are described. A new ligand‐induced pocket, S1′ ∗, is found in the zinc metalloproteinase. Pockets like S1′ ∗ have been successful targets for human metalloproteases. Conformationally‐strained ligands reliably induce S1′ ∗ in lethal factor. The lethal factor S1′ ∗ pocket is a new target for drug design against anthrax toxin.